Portrait of the Revitalization of Arabic Language Learning Using Technological Developments for the Future - Muhammad Solihin; M.Tholibin Azhari; Mujiburrahman; Abdul Aziz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The object is one of the discussions on the Future of Development of Arabic Language Learning Media and Technology which functions to form, among other things, learning media and improving the quality of teaching human resources so that they are professional, innovative and competitive. Arabic in Indonesia is one of the foreign languages studied in formal and non-formal educational institutions. Therefore, the author will examine, among other things, learning media and improving the quality of teaching human resources so that they are professional, innovative and competitive. Thus, so that the Arabic language learning process runs well, has competitiveness and is able to compete with other foreign language learning, it is necessary to master the Arabic language learning methodology. Another way is to be able to use modern internet-based learning media in accordance with the information technology era. Even though it is in a local educational institution, it is able to compete with other international educational institutions. On the other hand, according to Prananto Sukmajaya (an information technology expert) said that the urgent development of information technology has transformed the concept of computer-based education (CBE) into information technology-based education. Information technology can integrate computers, the internet and other information system facilities into tools that empower the teaching and learning process to be more creative, innovative and competitive.